“Ethnic Revival” in Globalizing World: The Example of Indigenous Political Movements in Latin America - S. M. Kretov (Vestnik MGIMO-Universiteta)
The article offers an inquiry into the problem of “ethnic revival” in politics against the background of the accelerated globalization processes through the example of the indigenous movements in Latin America. In particular, it explains how such global trends as the democratization and liberalization of social and political spheres, intensified activities of international institutions on the empowerment of disadvantaged social groups, the inclusion of ecological problems in national and international agendas, growing interest of international society to the social and political problems of developing countries have contributed to the intensification of political activities of the indigenous peoples in Latin America in the last 25 years.The indigenous political activism has taken radically different institutional forms and has led to diverse outcomes. For instance, in Mexico the indigenous peoples did not manage to create a viable sociopolitical force capable of advocating for their rights. In some other Latin America states, there are indigenous organizations that successfully promote the interests of native peoples. Moreover, in various countries the indigenous representatives are elected to national and local governments. In Colombia, Ecuador and Nicaragua the indigenous political parties were found, which, as long as other political forces, are participating in electoral processes and are delegating their representatives to public institutions. Whereas in case of Bolivia, the indigenous movement in alliance with left and progressive social organizations, has become the leading political force.The author gives an explanation why the political activism of the indigenous peoples in different Latin American countries has taken such forms and has contributed to such results. On the basis of the analysis of these political activities the conclusion is made about common features of political culture, self-identification and perception of social and political processes by the indigenous peoples of Latin America.